Gamelan Sistem Sepuluh Nada dalam Satu Gembyang untuk Olah Kreativitas Karawitan Bali - Hendra Santosa; Saptono . (PANTUN, 2019)
This article is part of the Competitive Grants study entitled “Prototipe Gamelan Sistem Sepuluh Nada dalam Satu Gembyang.” The concept of ten tones in one gembyang (oktav) has once been formulated by Raden Angga Mahyar Kusumadinata, Indonesian musicologist. In Balinese, gamelan scales with ten-tone system are wri!en in the Prakempa manuscript. This interesting musical concept has not been thoroughly investigated. The previous research has produced a prototype set of ten system gamelan tones in one gembyang whose try out uses the existing gending Bali.This research is expected to provide significant contribution in supporting the creativity of Karawitan artists.Balinese Karawitan Artists no longer need to carry a lot of gamelan to play all the Balinese gamelan since they are already represented in the gamelan of ten tones system in one gembyang.Keywords: gamelan, ten-tone, gembyang, prakempa